Psychometric properties evaluation of persian version of the maastricht clinical teaching questionnaire - Abdolghader Assarroudi; Roghayeh Zardosht (Wolters Kluwer Medknow Publications, 2023)
Background: Students are a significant source of data for the evaluation of clinical instructors' performance. This study was undertaken with the aim of adaptation and validation of the Persian version of the Maastricht Clinical Teaching Questionnaire (MCTQ). The main objective of the researchers in this study was to evaluation the psychometric properties of the Persian version of the Maastricht Clinical Training Questionnaire (P-MCTQ) in Iran, considering cultural and social differences. Materials and Methods: This methodological study was conducted from 2019 to 2021 at four teaching hospitals affiliated with Sabzevar University of Medical Sciences, Iran. Qualitative and quantitative face and content validity, and construct validity methods were used for the validity evaluation. Stability and internal consistency methods were used, respectively, for the reliability evaluation of the questionnaire. Exploratory Factor Analysis (EFA) stage, 264 students studying in the fields of nursing, midwifery, anesthesiology, operating room, emergency medicine, and laboratory sciences completed the P-MCTQ. Results: The value of scale-content validity index (0.92) is indicative of the overall content validity of the questionnaire. EFA extracted a single-factor structure that could explain the overall variance of the clinical education structure at about 76.61%. The alfa and intraclass correlation values were equal to 0.98 and 0.82, respectively, indicating the excellent internal consistency and high overall stability of the questionnaire. Conclusions: The P-MCTQ is a valid and reliable tool for the evaluation of the teaching performance of clinical instructors.